Accessing neurosurgical services in Africa: efforts, challenges, and recommendation. Issue 6 (19th November 2022) - Aderinto, Nicholas; Opanike, Joshua; Oladipo, Elizabeth; Olakanmi, Damilare; Adepoju, Oluwatosin
Abstract : Africa faces a dire need for neurosurgical services. Despite the high burden of neurosurgical conditions, there is disproportionately low access to neurosurgical services. Barriers to seeking neurosurgical services in Africa are mainly due to socioeconomic factors of cost, lack of infrastructure, and human resources, which continue to be at the heart of poor delivery of health care generally in the region. These barriers are more profound because neurosurgery is highly specialized and relies on a web of interrelating processes, including neuroimaging, neuro-anesthesia, operating room peculiarities, specialized nursing care, and rehabilitation services. While most efforts at improving the health needs of Africans have been tailored toward battling infectious diseases, health stakeholders in Africa must look toward improving the current state of access to neurosurgical services. If this burden is not attended to, there is a risk that overwhelmed health care systems would result in erosion in efforts to improve the provision of essential neurosurgical services.